BRG1‐mediated immune tolerance: facilitation of Treg activation and partial independence of chromatin remodelling. (15th January 2013) - Chaiyachati, Barbara H; Jani, Anant; Wan, Yisong; Huang, Haichang; Flavell, Richard; Chi, Tian
<x xml:space="preserve">Abstract</x> Treg activation in response to environmental cues is necessary for regulatory T cells (Tregs) to suppress inflammation, but little is known about the transcription mechanisms controlling Treg activation. We report that despite the known proinflammatory role of the chromatin‐remodelling factor BRG1 in CD4 cells, deleting Brg1 in all αβ T cell lineages led to fatal inflammation, which reflected essential roles of BRG1 in Tregs. Brg1 deletion impaired Treg activation, concomitant with the onset of the inflammation. Remarkably, as the inflammation progressed, Tregs became increasingly activated, but the activation levels could not catch up with the severity of inflammation. In vitro assays indicate that BRG1 regulates a subset of TCR target genes including multiple chemokine receptor genes. Finally, using a method that can create littermates bearing either a tissue‐specific point mutation or deletion, we found the BRG1 ATPase activity partially dispensable for BRG1 function. Collectively, these data suggest that BRG1 acts in part via remodelling‐independent functions to sensitize Tregs to inflammatory cues, thus allowing Tregs to promptly and effectively suppress autoimmunity.